Rancang Bangun Sistem Pengelolaan Kursus Dan Pelatihan Pada LKP Dotnet Computindo - Yusup Undara; Martini Martini; Hidayanti Murtina (UNIVERSITAS INDO GLOBAL MANDIRI)
The administrative process for the Lembaga Kursus dan Pelatihan (LKP) is important in the smooth implementation of training programs. Recording of training data that is properly archived is also a matter that needs to be considered for the smooth running of training and decision making. A LKP needs complete training program data to attract the attention of prospective trainees. Currently, the training registration process and training data recording at LKP Dotnet Computindo are still using manual recording. The information disseminated is also limited to people who are looking for and need a training place or course. Another problem is that prospective trainees find it difficult to register for training programs and find information about the type of training that will be running. On the other hand, training institution managers also experience difficulties in managing training data that support the running of the training program. Therefore we need a web-based application that can make it easier to register for training and can manage other supporting training data. In this application, software development uses the Waterfall model which is carried out in stages, and the PHP programming language. With this web-based application, it is hoped that training participants and instructors will no longer experience difficulties in finding training information that will be held at LKP Dotnet Computindo. Training managers also no longer experience difficulties in managing existing training data, so they no longer need to store data manually. Keywords : Training program, Waterfall method, training participants and teachers